Second International Gay Youth Congress : Dublin 7th - 14th july 1985. (Dublin : Hirschfeld Centre, 1985)
Fonds Suzan Daniel (FSD)
Omslag vermeldt : Building a future : a task for gay youth groups
Engels
Brochure